Realizing Public Welfare from the Nation's Kitchen: A Fiqh Siyasah Perspective on the Makan Bergizi Gratis (MBG) and Its Impact on the Muslim Community - Ananda Bagus Pradita; Galih Sepwantoro; Vina Auliya; Imoh Emmanuel Uwem (Islamic Research Publiser, 2025)
The Makan Bergizi Gratis (MBG) program is a government social policy designed to enhance public welfare, particularly for low-income groups vulnerable to malnutrition and poverty. The program functions not only as food assistance but also as an instrument of economic redistribution and social solidarity at the grassroots level. From the perspective of fiqh siyasah (Islamic political jurisprudence), public policy must be based on the principles of justice (al-ʿadālah) and public welfare (al-maṣlaḥah al-ʿāmmah), ensuring equitable and sustainable prosperity for society. This research uses a qualitative field approach. Data were obtained through in-depth interviews with beneficiaries, school administrators, religious leaders, and local government officials involved in implementing the MBG program. Direct observations were conducted in several schools and Muslim communities to gain empirical insights into the program’s actual impact. Secondary sources, including policy documents, government regulations, and relevant scholarly literature, complemented primary data and strengthened analytical interpretation. The findings show that the MBG program has reduced the economic burden on low-income families, increased children’s school attendance, and encouraged stronger social cohesion. Nevertheless, problems remain, including distribution delays, limited budgets, and insufficient transparency in fund management. Based on a fiqh siyasah analysis, the success of public policy depends on integrity (amānah), accountability, and just governance. Therefore, participatory and transparent mechanisms are essential to ensure that the MBG program truly promotes maṣlaḥah in line with the maqāṣid al-sharī‘ah. The academic contribution of this study lies in its attempt to connect empirical evidence with the theoretical framework of fiqh siyasah.